Who Serves the Poor? An Equity Analysis of Public and Private Providers of Family Planning and Child Health Services in Kenya - Chakraborty, Nirali M.; Montagu, Dominic; Wanderi, Joyce; Oduor, Christine (Frontiers in Public Health, 2019)
Understanding differences in the wealth status of patients can inform planning decisions aimed at providing affordable access to high quality care to all. This study assesses differences in the wealth status of clients of family planning and child health services by health sector. It also describes reason for facility choice, cost of services and the proportion of additional clients of these services, and assesses if there are any differences by health sector. A cross-sectional survey of 2173 clients from 96 health facilities in urban areas of 6 counties in Kenya was conducted, stratified by health facility type. The 4 strata were public, faith-based, private for profit, and social franchise. Client wealth was benchmarked to the national and urban population of the 2014 Kenya DHS, and assessed using the EquityTool. There were significant differences in the client wealth distribution between facility types, and public sector facilities served a significantly higher proportion of poor clients than other types of facilities. In all three non-public facility types, more than 25% of clients were from the poorest two wealth quintiles, without significant differences between facility types. No facility type stands out as expanding access to health services more than another. Results show that social franchises do better at reaching the poor than earlier studies have indicated, though not as well as faith-based and public facilities. Findings suggest that private providers remain important within the larger health system, more so for family planning than childhood illness management. In urban areas with significant facility choice, this study quantifies differences in client wealth across 4 health sectors. Incorporating these findings into policy and programmatic interventions can improve equity in access to and use of quality health services.